Brucellosis: Review on the Recent Trends in Pathogenicity and Laboratory Diagnosis - Christopher, Supriya; L., Umapathy B; L., Ravikumar K (Journal of Laboratory Physicians, 2010)
Brucellosis is a zoonotic infection transmitted from animals to humans by the ingestion of infected food products, direct contact with an infected animal or inhalation of aerosols. The last method is remarkably efficient given the relatively low concentration of organisms (10 – 100 bacteria) needed to establish infection in humans, and has brought renewed attention to this old disease. Brucella is a facultative intracellular pathogen that has the ability to survive and multiply in the phagocytes and cause abortion in cattle and undulant fever in humans. Brucella spp particularly B. melitensis, B. abortus, and B. suis represent a significant public health concern. At present, B. melitensis is the principle cause of human brucellosis in India. Molecular studies have demonstrated the phylogenetic affiliation of Brucella to Agrobacterium, Ochrobactrum, and Rhizobium. Human brucellosis still presents scientists and clinicians with several challenges, with regard to the understanding of its pathogenic mechanism, severity, progression, and development of improved treatment regimens. Molecular studies have now highlighted the pathogenesis of Brucella, for the development of newer diagnostic tools that will be useful in developing countries where brucellosis is a common, but often a neglected disease. This review compiles all these issues in general and the pathogenicity and newer diagnostic tools in particular.
Keywords: Brucellosis; lipopolysaccharide; virulence; zoonotic disease; serodiagnosis